Left behind: The potential impact of CFTR modulators on racial and ethnic disparities in cystic fibrosis. (June 2022) - McGarry, Meghan E.; Gibb, Elizabeth R.; Oates, Gabriela R.; Schechter, Michael S.
Highlights: Current CF disparities are primarily due to adverse social (rather than genetic) determinants of health. CF patients of non-European descent are more likely to have mutations unresponsive to modulator treatment. Therefore the advent of CFTR modulator therapies may lead to genetically based disparities. People with CF in less economically developed nations have restricted access to CFTR modulators. CF Newborn screening algorithms should be sensitive to mutations prevalent in diverse non-European populations. Abstract: The advent of CFTR modulators, a genomic specific medication, revolutionized the treatment of CF for many patients. However, given that these therapeutics were only developed for specific CFTR mutations, not all people with CF have access to such disease-modifying drugs. Racial and ethnic minority groups are less likely to have CFTR mutations that are approved for CFTR modulators. This exclusion has the potential to widen existing health disparities.